Sodium Sulphite As A Sulphide Depressant-Theory And Practice At The CSA Mine Concentrator, Cobar, NSW (The Australasian Institute of Mining and Metallurgy, 1983)
Cobar Mines Pty. Limited (CMPL) uses sodium sulphite as the principal depressant to attain selectivity in copper flotation prior to sequential recovery of lead and zinc. The usage of sodium sulphite is examined both from a theorectical viewpoint ana from the manner in which the copper circuit at (MPL has developed. The results of relatively recent investigations, both in the laboratory ana the plant, are discussed aria shown to support the present operating Techniques.